Parables for preachers - Reid, Barbara E. (Collegeville, Minn : Liturgical Press, 1999)
Contents: [1] Year A. The Gospel of Matthew - - [2] Year B. The Gospel of Mark - - [3] Year C. The Gospel of Luke
Includes bibliographical references
Keywords: Jesus Christ -- Parables -- Homiletical use; Bible. N.T. Mark -- Criticism, interpretation, etc; Bible. N.T. Mark -- Homiletical use; Lectionary preaching -- Catholic church; Bible. N.T. Matthew -- Criticism, interpretation, etc; Bible. N.T. Matthew -- Homiletical use; Bible. N.T. Luke -- Criticism, interpretation, etc; Bible. N.T. Luke -- Homilitical use